PENINGKATAN PEMAHAMAN SISWA SMK 3 KOTA SEMARANG MENGENAI PENYELENGGARAAN PERLINDUNGAN ANAK - surayda, helen intania (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2021)
The law is basically a reflection of human rights that is no longer seen as a mere defense but also a protection of citizens. This regulatory product will protect citizens. In fact, children cannot protect themselves from various words of loss, mental and social and in various lives. Based on KPA data for regions in Central Java Province as many as 957 cases of child protection occurred in the period 2011-2016. Of the 8 child protection clusters, the 4 highest rankings consist of 135 cases of advanced children with the law, 81 cases of family and alternative education, 5 cases of health and napza and 49 cases of education. According to dp3akb data of Central Java Province in August 2020 there were 76 cases of children. Meanwhile, data on DP3A in Semarang in 2019 reached 5 cases. Based on the above thoughts and data, we as a Community Development Team feel that there needs to be real action through legal counseling activities on child protection in the Semarang area, namely SMK 3 Semarang City. Berbed this can be formulated problems in this community loving activity is to raise students smk 3 Semarang about "Child Protection City". This Community Detractor activity is conducted by pre-test method, lectures, discussions, Q&A and post test. In this activity, smk 3 students obtain information and information about child protection. The results of this activity have, before the activity, smk 3 students have not understood and understood, and after counseling smk 3 students increased insights on child protection services, it is terbib he well understood from the general 40 participants by 53.07%.Keywords: Organizing, Protection, Children.